On expand-contract plasticity in quasi-metric spaces - Zavarzina, O.O. (Carpathian Mathematical Publications, 2023)
It is known that if any function acting from precompact metric space to itself increases the distance between some pair of points then it must decrease distance between some other pair of points. We show that this is not the case for quasi-metric spaces. After that, we present some sufficient conditions under which the previous property holds true for hereditarily precompact quasi-metric spaces.